Factors mediating HIV risk among female sex workers in Europe: a systematic review and ecological analysis. Issue 7 (24th July 2013) - Platt, Lucy; Jolley, Emma; Rhodes, Tim; Hope, Vivian; Latypov, Alisher; Reynolds, Lucy; Wilson, David
Abstract : Objectives: We reviewed the epidemiology of HIV and selected sexually transmitted infections (STIs) among female sex workers (FSWs) in WHO-defined Europe. There were three objectives: (1) to assess the prevalence of HIV and STIs (chlamydia, syphilis and gonorrhoea); (2) to describe structural and individual-level risk factors associated with prevalence and (3) to examine the relationship between structural-level factors and national estimates of HIV prevalence among FSWs. Design: A systematic search of published and unpublished literature measuring HIV/STIs and risk factors among FSWs, identified through electronic databases published since 2005. 'Best' estimates of HIV prevalence were calculated from the systematic review to provide national level estimates of HIV. Associations between HIV prevalence and selected structural-level indicators were assessed using linear regression models. Studies reviewed: Of the 1993 papers identified in the search, 73 peer-reviewed and grey literature documents were identified as meeting our criteria of which 63 papers provided unique estimates of HIV and STI prevalence and nine reported multivariate risk factors for HIV/STI among FSWs. Results: HIV in Europe remains low among FSWs who do not inject drugs (<1%), but STIs are high, particularly syphilis in the East and gonorrhoea. FSWs experience high levels of violence and structural risk factors associated with HIV, including lack of access to services and working on the street. Linear regression models showed HIV among FSWs to link with injecting drug use and imprisonment. Conclusions: Findings show that HIV prevention interventions should be nested inside strategies that address the social welfare of sex workers, highlighting in turn the need to target the social determinants of health and inequality, including regarding access to services, experience of violence and migration. Future epidemiological and intervention studies of HIV among vulnerable populations need to better systematically delineate how microenvironmental and macroenvironmental factors combine to increase or reduce HIV/STI risk.